Šanghajska organizacija za sodelovanje v središču mednarodnega vozlišča - Golob, Damjan (Vojaškošolski zbornik, 2024)
The Shanghai Cooperation Organisation is one of the largest international regional organizations, with the geographical area of its member states extending beyond Central Asia. The organization’s members are driven by different interests, particularly at the political, security and economic levels. Here, Russia and China in particular stand out, pursuing some common interests (e.g. power projection in Central Asia and in the wider region, a multipolar world order), but also some diverging ones (Russia: an anti-Western stance, security and military aspects; China: economic cooperation). Although the organization has considerable influence on shaping the world order, it is also faced with challenges concerning policy coherence, as reflected in the issue of membership expansion.
Keywords: China; Kitajska; Mednarodne organizacije; Mednarodni odnosi; multipolarity; multipolarnost; Regionalizem (mednarodna skupnost); Rusija; Russia; Shanghai Cooperation Organisation; svetovni red; Šanghajska organizacija za sodelovanje; Vojaška politika; world order